Applicability of the Online Short Spatial Ability Battery to university students testing - K. V. Bartseva; M. V. Likhanov; E. L. Soldatova; E. S. Tsigeman; E. A. Alenina; Y. Kovas (Russian State Vocational Pedagogical University, 2023)
Introduction. Multiple studies advocate an importance of spatial abilities (SA) for educational and occupational success, especially in STEM. Recently an Online Short Spatial Ability Battery (OSSAB) was developed and normed for SA testing in adolescents. The battery includes mechanical reasoning, paper folding, pattern assembly, and shape rotation tests. The battery has shown good psychometric characteristics (high reliability and validity, low redundancy, discriminative power), and is available in open access and free to use.Aim. The present research aims: 1) to examine the applicability of the OSSAB for university student testing; 2) to describe its psychometric properties and structure; and 3) to investigate links between SA and educational performance.Methods. A total of 772 university students (aged from 18 to 26, mean age (SD) = 19.55 (1.51), 63.1% females) participated in the study. Participants provided information about their age, gender, university major, and academic achievement, and completed a battery of tests that included the OSSAB tests.Results. The study reports psychometric norms for using the OSSAB in university students. Students' performance in the OSSAB was similar to that shown in previous research in adolescents in terms of means and variance. The OSSAB showed adequate psychometric properties in this sample: no floor or ceiling effects; low redundancy; moderate to high internal consistency; high discriminative power across university majors; and high external validity. The results indicated that around 6% of the students showed very high levels of SA (higher than 1.5 SD above the mean), and around 8% of students showed very low levels of SA (lower than 1.5 SD below mean). In addition, the OSSAB scores were linked to educational profile choice and exam scores, with small-to-medium effect sizes.Scientific novelty. The study provides psychometric norms for a short online open measure of spatial ability in university students.Practical significance. The OSSAB can be used to provide individual recommendations to students (e.g. SA training), to identify spatially gifted students, and for research purposes in university contexts.